WOMEN SUBORDINATION IN TEMPURUNG BY OKA RUSMINI - Agustina, Hiqma Nur (Journal of English Educational Study (JEES), 2024)
Women experience a lot of repression from culture, gender stereotypes, and the social environment in society. The depiction of the women's suffering was written in a novel entitled Tempurung by Oka Rusmini. The aims of this research are (1) to identify Balinese women's marriages and the ownership of their bodies that never belong to them; and (2) to identify the gender stereotype that often makes Balinese women not have the right to determine their lives. This study uses gender and patriarchy concept, qualitative and library methods. The results of the study are (1) the women characters in the novel are the victims of the culture and rules in the society; (2) the gender stereotype means women characters can only surrender and not dare to rebel. They are trapped in the culture and tradition that makes them suffer and speechless in their whole life. Gender stereotypes make them silent and finally give up on the culture surrounding them. Their lives and deaths are a fate that must be accepted without having the right and voice to be themselves. The results of the research strengthened the previous research about women's subordination because of culture, gender stereotypes, and social environment. They are alive, but they do not have the right to determine their body and soul.Keywords: Balinese women, culture repression, gender stereotype, subordination, social environment